2007
DOI: 10.1029/2007gl029948
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime warming of an Arctic shelf in response to large‐scale atmospheric circulation

Abstract: Observations on the West Spitsbergen Shelf have shown that the dynamic response of the shelf to wind forcing has a profound effect on the heat content of the water. Hydrographic and atmospheric data have been analysed with respect to the relative importance of surface heat fluxes and advective processes on ocean temperature. During the Arctic winter of 2005/06 periods of sustained along‐shelf winds generated upwelling and cross‐shelf exchange causing extensive flooding of the coastal waters with warm Atlantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
215
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 246 publications
(224 citation statements)
references
References 23 publications
9
215
0
Order By: Relevance
“…They concluded that despite low regional air temperatures in February 2006 heat released over the entire shelf system prevented ice formation. Consequently, the dynamic response to wind direction potentially had a greater effect on shelf water temperatures, and thus sea ice formation particularly in the Isfjorden, than changes in air temperature (Cottier et al, 2007). At the same time an extremely large, high-pressure system over Russia and Eastern Europe blocked the usual pathway of low-pressure systems to Norway and into the Barents Sea, thus directing them towards the Fram Strait and the Eurasian Basin (Cottier et al, 2007).…”
Section: / Arctic Antarctic and Alpine Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that despite low regional air temperatures in February 2006 heat released over the entire shelf system prevented ice formation. Consequently, the dynamic response to wind direction potentially had a greater effect on shelf water temperatures, and thus sea ice formation particularly in the Isfjorden, than changes in air temperature (Cottier et al, 2007). At the same time an extremely large, high-pressure system over Russia and Eastern Europe blocked the usual pathway of low-pressure systems to Norway and into the Barents Sea, thus directing them towards the Fram Strait and the Eurasian Basin (Cottier et al, 2007).…”
Section: / Arctic Antarctic and Alpine Researchmentioning
confidence: 99%
“…Consequently, the dynamic response to wind direction potentially had a greater effect on shelf water temperatures, and thus sea ice formation particularly in the Isfjorden, than changes in air temperature (Cottier et al, 2007). At the same time an extremely large, high-pressure system over Russia and Eastern Europe blocked the usual pathway of low-pressure systems to Norway and into the Barents Sea, thus directing them towards the Fram Strait and the Eurasian Basin (Cottier et al, 2007). Rogers et al (2005) found during relatively mild winters, cyclone frequency increased over the Fram Strait area immediately west of Svalbard, bringing a warm sector over the islands, when high pressure occurred over Scandinavia and the Barents Sea, whereas relatively cold winters had increased cyclone frequency in the Barents Sea.…”
Section: / Arctic Antarctic and Alpine Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the dominating phytoplankton species during the bloom, the pattern seems more distinct between Arctic and Atlantic years. When the fjord is dominated by Arctic water, a hydrographical front at the entrance of the fjord separates the fjord system from the Atlantic water on the shelf (Svendsen et al 2002;Cottier et al 2007). Willis et al (2006) demonstrated that there was a close relationship between water mass advection into Kongsfjorden and changes in zooplankton community structure.…”
Section: Water Masses and Ice Conditionsmentioning
confidence: 99%
“…Over the central Arctic Ocean, small-scale processes are somewhat more tractable than near the coasts and continental shelves. In the latter regions, processes have a more profound three-dimensional structure, including orographic influences on the air flow and, likewise, influences of the bottom topography and river discharge on local stratification and circulation in fjords and coastal waters (Cottier et al, 2007). In all regions, small-scale processes (e.g.…”
mentioning
confidence: 99%